On the occurrence of Laurencia caraibica (Ceramiales, Rhodophyta) in Atol das Rocas, Brazil - Toyota Fujii, Mutue; Villaça, Roberto (HIDROBIOLÓGICA, 2017)
Laurencia caraibica P.C. Silva is being referred occurring in Atol das Rocas, a small island located about 147 miles off Brazilian northeastern coast. The specimens are characterized by the soft, reduced size thalli with four periaxial cells per each axial segment and tetrasporangia in parallel arrangement; presence of lenticular thickenings in the wall of the medullary cells; epidermal cells near the apex not projected beyond the surface of the thalli; presence of anastomose between branches and the occurrence of secondary pit connections between epidermal cells. In this paper, previously unknown detailed morphological characters are presented and compared to related species.